Supplementing powdered high-fiber foods to alter gut microbial metabolism for colorectal cancer prevention - Sheflin, Amy Marie, author; Weir, Tiffany, advisor; Broeckling, Corey, committee member; Melby, Chris, committee member; Pagliassotti, Michael, committee member (Colorado State University. Libraries, 2016)
Trillions of microorganisms populate the human digestive tract and enhance immunity, improve digestion and inhibit pathogens when in healthy balance. However, a disruption of gut community balance is associated with a number of diseases including colorectal cancer (CRC). The purpose of this research was to investigate supplementation with two high-fiber foods, heat stabilized rice bran (SRB) and cooked navy bean powder (NBP), for potential to favorably alter the intestinal environment for CRC prevention. Study 1 aimed to assess differences in stool microbiota and associated metabolites in healthy individuals versus those diagnosed with CRC. Next, two pilot dietary interventions were undertaken (Study 2 and 3), one in healthy individuals and another in CRC survivors. Both pilot studies provided diets supplemented with SRB or NBP or macronutrient matched control foods and changes in stool microbiota and associated metabolites were assessed at baseline and after 2 and 4 weeks. The collective body of this research supports the hypothesis that gut microbiota and their metabolites differ with respect to CRC and that intervention with SRB or NBP can alter this profile. Despite similar increases in dietary fiber intake, SRB induced more significant change to gut microbiota and metabolites possibly due to differing chemical composition of plant fibers. Relative to NBP, SRB is rich in arabinoxylans, which structurally mimic the protective mucins lining the intestinal surface. Changes in both microbiota and metabolites observed with SRB supplementation are consistent with enrichment of glycan-foraging bacteria able to switch between dietary glycans (arabinoxylans in this case) and host glycans for energy. Acetate and propionate, potentially beneficial byproducts of microbial fermentation of glycans and other fiber components, increased at 2 weeks in CRC survivors. However, some of the observed changes did not persist at 4 weeks and further research is necessary to determine if more lasting changes are possible with these dietary interventions, as well as whether these altered microbial/metabolite profiles are associated with reduced risk of CRC incidence and recurrence.